2006
DOI: 10.1007/s00127-006-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Family support predicts psychiatric medication usage among Mexican American individuals with schizophrenia

Abstract: Findings suggest that efforts to improve medication usage among Mexican American individuals with schizophrenia should take into account social supportive factors such as instrumental or directive, hands-on assistance from family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 28 publications
2
30
0
2
Order By: Relevance
“…Study objectives varied, with some focusing specifically on adherence (1, 6, 41, 4447, 49, 5160) while others measured adherence as part of studies addressing different questions. Geographically, eight were based in California (6, 42, 43, 47, 48, 50, 54, 55), two in Texas (41, 51), one in New Mexico (52), one in New York (49), one in Connecticut (56), one in Ohio (40), and four were from Veteran’s Administration National Registries (46, 5860), and three were national studies (1, 45, 57).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study objectives varied, with some focusing specifically on adherence (1, 6, 41, 4447, 49, 5160) while others measured adherence as part of studies addressing different questions. Geographically, eight were based in California (6, 42, 43, 47, 48, 50, 54, 55), two in Texas (41, 51), one in New Mexico (52), one in New York (49), one in Connecticut (56), one in Ohio (40), and four were from Veteran’s Administration National Registries (46, 5860), and three were national studies (1, 45, 57).…”
Section: Resultsmentioning
confidence: 99%
“…One study identified problems with a drug of abuse (45) as a risk factor for nonadherence, however, another study found that abstinence from street drugs (marijuana was excluded from the definition) was not significantly related to adherence (44). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations